PENGEMBANGAN MEDIA LITERACY LAYANAN BK TEKNIK CINEMA THERAPY BERDASARKAN MODEL GAGNE UNTUK MENGANTISIPASI PERGAULAN BEBAS - Frezy Paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2023)
This study aims to describe the initial conditions of media literacy using cinema therapy techniques to anticipate free association among students at SMK Negeri 1 Lolayan, Bolaang Mongondow Regency, to create a guidebook for the use of cinema therapy technique media literacy in Guidance and Counseling services based on the Gagne model to anticipate promiscuity among students of SMK Negeri 1 Lolayan and knowing the steps for developing and effectiveness of media literacy using cinema therapy techniques to anticipate free association among students of SMK Negeri 1 Lolayan, Bolaang Mongondow Regency. This research approach is a type of research development or Research and Development (R&D). The data used is qualitative data. Based on the data analysis performed, the results of the post-test showed that 26 students completed promiscuity problems with a mastery proportion of 86.6%. Of these proportions, media literacy using cinema therapy techniques is said to be effective.